Effect of long term fertilization on soil fertility and yield of rice in Cauvery Delta Zone - Rahale, C Sharmila; Balasubramanian, P; Bharani, A (ORYZA-An International Journal of Rice, 2018)
A long term fertility experiment was initiated in 1992 to study the effect of inorganic, organic fertilizers, agro chemicals and biofertilizers on productivity of a rice -rice system with respect to changes in soil fertility. Results of five years (2012-2017) experimentation revealed that the treatment receiving continuous application of NPK at 125:50:50 kg/ha in Kharif and 150:60:60 kg/ha in Rabi season along with green manure at 6.25 t/ha in Kharif and 12.5 t/ha of FYM in Rabi and gypsum at 500 kg ha-1 both in Kharif an Rabi seasons respectively recorded significantly higher grain yield in both the seasons consecutively for five years. At the end of the 50th rice crop, the soil chemical properties like pH, EC, organic C, available N,P and K exhibited s significant differences due to various treatments imposed. The values of nutrient uptake by rice crop also showed significant differences among various treatments. The results suggest the need of integrated nutrient management practices to sustain in rice productivity in the heavy soils of Cauvery Delta Zone (CDZ).